Penentuan Kriteria Pengukuran Indikator Kinerja Penyelenggaraan Diklat Berbasis Kompetensi Menggunakan Metode Focus Group Discussion - Rohmatulloh, Rohmatulloh; Shiddiq, Julian Ambassadur (Jurnal Ilmiah Teknik Industri, 2017)
The formulation of performance indicators is good and meaningful must meet the criteria CREAM (clear, relevant, economic, adequate, and monitorable). In practice, it is often found performance indicators can not be applied because it has a variety of interpretations in the criteria of measurement. The problem is discussed using focus group method (FG). The results of the discussion have succeeded in identifying and consensusing the six criteria for measuring the key performance indicators (KPI) for the implementation of competency-based training, ie training needs analysis, syllabus curriculum, modules, training implementation guidelines, evaluation of training, and evaluation of training implementation (satisfaction and learning). The use of the FG method in this study is effective enough to generate many ideas and the participation of internal stakeholders in solving the problem. The success of FG is highly dependent on pre-discussion planning, especially the deepening of the issues studied and the determination of data sources or participants, who understand the issues being discussed.